2020
DOI: 10.30935/ojcmt/8498
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions about the Impact of Moodle in the Educational Field Considering Data Science

Abstract: Today, Learning Management Systems (LMS) such as Moodle facilitate the teaching-learning process, promote the organization of creative activities from anywhere and allow the active participation of the students before, during and after the face-to-face sessions. The objective of this quantitative research is to analyze the teachers' perceptions about the impact of Moodle in the educational field considering data science and machine learning. The independent variable is the use of Moodle during the organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…During the 21st century, technological tools are causing that universities update the teaching-learning process in order to meet the demands of the students about the use of new educational methods and strategies (Doo et al, 2020;Papadakis et al, 2018;Pilli & Admiraal, 2016;Zhou, 2017). For example, the incorporation of Learning Management Systems (LMS) such as Moodle in the educational field favors the interaction and communication at any time through mobile phones (Papadakis et al, 2017;Salas-Rueda et al, 2020). In addition, universities use virtual reality together with MOOCs to improve the teaching-learning conditions (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…During the 21st century, technological tools are causing that universities update the teaching-learning process in order to meet the demands of the students about the use of new educational methods and strategies (Doo et al, 2020;Papadakis et al, 2018;Pilli & Admiraal, 2016;Zhou, 2017). For example, the incorporation of Learning Management Systems (LMS) such as Moodle in the educational field favors the interaction and communication at any time through mobile phones (Papadakis et al, 2017;Salas-Rueda et al, 2020). In addition, universities use virtual reality together with MOOCs to improve the teaching-learning conditions (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Prior experience with Moodle was found to influence teachers' perceptions of the platform. Salas-Rueda et al (2020) reported that teachers' perceptions of Moodle varied depending on their level of experience using the platform, with more experienced teachers having a more positive perception of Moodle's impact. The same finding regarding teachers' prior experience with using Moodle was reported by Uzunboylu et al (2021) in Turkish universities.…”
Section: Teachers' Perspectives In Using Moodle During the Pandemicmentioning
confidence: 99%
“…Finally, research during the pandemic showed that teachers perceived Moodle positively because of its ease of use for both teachers and students. Antuñano et al ( 2022), Salashttp://ijlter.org/index.php/ijlter Rueda et al (2020), andTaamneh et al (2022) reported that teachers found Moodle helpful during the pandemic for its communication features and assessment tools.…”
Section: Teachers' Perspectives In Using Moodle During the Pandemicmentioning
confidence: 99%
“…In another research, Oproiu (2015) stated that Moodle platform, which is becoming increasingly popular in Romania, serves not only as a tool for educators looking to improve the quality of online courses, but also as a tool for students looking to make their learning more convenient. Zabolotniaia, Cheng, Dorozhkin and Lyzhin (2020) stated in their article that possibilities of employing Moodle features to promote the proper applicationat higher educational institution's innovative policy are addressed. The construction of an elevated data and knowledge system is a critical and crucial problem for higher education institutions with in context of mobile transformation of social sector.…”
Section: Introductionmentioning
confidence: 99%